2003
DOI: 10.1002/bem.10190
|View full text |Cite
|
Sign up to set email alerts
|

Comments on “Bioelectrical parameters of the whole human body obtained through bioelectrical impedance analysis”

Abstract: The question of the existence of inductive phenomena in the human body that could affect bioimpedance measurements has been raised several times through the history of this technique. In a recent paper from Lafargue et al. [2002], an inductor is introduced in the so-called Cole-Fricke-Cole (CFC) model in order to fit experimental data. The inclusion of inductors in the low frequency range (f < 10 MHz) should not be required to explain any measured impedance data from the whole human body. In addition, the pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Inductive properties can also be found in biological tissue, but as commented by Riu (2004) the inductance at frequencies below 10 MHz is usually insignificantly low compared to the resistance and reactance commonly found in the human body. The current flows through the cells if the frequency is sufficiently high.…”
Section: Electrical Bioimpedancementioning
confidence: 99%
“…Inductive properties can also be found in biological tissue, but as commented by Riu (2004) the inductance at frequencies below 10 MHz is usually insignificantly low compared to the resistance and reactance commonly found in the human body. The current flows through the cells if the frequency is sufficiently high.…”
Section: Electrical Bioimpedancementioning
confidence: 99%
“…The positive phase angle seen in the MHz range can be interpreted as if the veins demonstrate inductive properties. However, studies have shown that the existence of inductive properties in tissue samples and cell membranes under stable conditions in passive bioimpedance measurements is not very likely (Cole 1972, Riu 2004). Nevertheless, the positive phase angle does not need to be a sign of measurement error and can be caused by the contribution of self-inductance when measuring low impedance values (<50Ω) at high frequencies, such as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…This lipid bilayer cell membrane is semi-permeable, due to which it has a high capacitance and which produces capacitive reactance [25], [26], [27]. Although biological cells and tissues may have inductive properties, inductance is much lower at low frequencies than resistance and reactance, so it is often overlooked [28]. Thus, biological cells or tissue's complex bioimpedance is the contributions from both frequency-dependent capacitance and conductance [21], [29], [30], [31], [32], [33].…”
Section: A Basics and Origin Of Bio-impedancementioning
confidence: 99%